MicroRNA: New Era for Therapeutic Strategy in Ischaemic Heart Disease - Mitra, Sarmistha; Hossain, Md. Kamrul (Journal of Hypertension and Cardiology, 2017)
Over the last few decades, many research works highlighted the role of miRNAs on cardiac diseases. Ischaemic heart disease (IHD) or coronary heart disease is a condition that is mainly caused by atherosclerosis. It has been established that microribonucleic acids regulate many factors that are involved in the development and pathophysiology of IHD. As a result, there are great potential opportunities for miRNAs to be used as a biomarker for disease differentiation, as well as novel drug targets or therapeutics for the treatment and also as a diagnostic approach. As it is now evident that miRNAs play critical roles in the disease mechanisms, this review article tried to focus on the pathway, in which; the miRNAs stimulate the IHD to develop. By understanding the mechanisms, it will be possible to present a complete strategy of IHD treatment and also solving all the impediments that are highlighted in this article. Still, there are a number of limitations and obstacles on the way of developing a proper therapeutic approach that can be approved and well accepted. This review is mainly dependent on the potential of miRNAs as a promising arena on the field of cardiac treatment and the possible obstacles that are needed to be explored and overcome.
Keywords: miRNA; Ischaemic Heart Disease; Therapeutics